PENGARUH MANAJEMEN KESEIMBANGAN CAIRAN BERBASIS SMARTPHONE TERHADAP KEMAMPUAN SELF-CARE PASIEN PENYAKIT GINJAL KRONIS DENGAN HEMODIALISIS DI RST dr. SOEDJONO MAGELANG - Solehan, Fandi; supriyatno, Heru; sunarmi, sunarmi; Sarwono, Bambang (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Chronic kidney disease (CKD) is a global health issue with a steadily increasing prevalence. One of the main challenges for hemodialysis patients is the increase in interdialytic weight gain (IDWG) due to fluid imbalance. Effective fluid management is crucial for improving patients' self-care abilities, one of which is through the use of smartphone technology. The objective of this study was to determine the effect of using a smartphone based self-care management application on improving self-care management skills in maintaining Interdialytic Weight Gain (IDWG) in patients with chronic kidney disease undergoing hemodialysis at RST dr. Soedjono Magelang.The study design was quasi-experimental with a pretest-posttest design and a control group. The study was conducted at dr. Soedjono General Hospital in Magelang with a total of 56 participants, divided into two groups: 28 in the experimental group and 28 in the control group. The sample was selected using purposive sampling. The intervention involved the use of a smartphone-based fluid management app over a specific period. Data analysis was performed using a paired t-test.The results showed a significant improvement in self-care ability after the app intervention, with a p-value of 0.000 (p < 0.05). This indicates that the use of a smartphone app effectively supports fluid management in CKD patients.In conclusion, smartphone-based self-care applications have a positive effect on improving the self-care abilities of PGK patients undergoing hemodialysis. The use of smartphone-based fluid management self-care applications needs to be promoted.